Combining Organocatalysis and Lanthanide Catalysis: A Sequential One‐Pot Quadruple Reaction Sequence/Hetero‐Diels–Alder Asymmetric Synthesis of Functionalized Tricycles. Issue 52 (23rd November 2016) - Dochain, Simon; Vetica, Fabrizio; Puttreddy, Rakesh; Rissanen, Kari; Enders, Dieter
Abstract: A stereoselective one‐pot synthesis of functionalized complex tricyclic polyethers has been achieved using the combination of secondary amine and lanthanide catalysis. This one‐pot quadruple reaction/Hetero‐Diels–Alder sequence gave good yields (per step) as well as excellent diastereo‐ and enantioselectivities. Furthermore, the particular combination of lanthanide complexes with organocatalysis is one of the first examples described for sequential catalysis. Abstract : Targeting complexity : A unique combination of organocatalysis with lanthanide catalysis directly leads to complex tricyclic structures from readily available and simple compounds. Six new bonds and six stereocenters are formed with virtually complete stereoselectivity in this multicomponent one‐pot procedure. fod=2, 2‐dimethyl‐6, 6, 7, 7, 8, 8, 8‐heptafluorooctane‐3, 5‐dionato.